2020
DOI: 10.24875/rmu.19000101
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory impairment in persons with multiple sclerosis: A cross-sectional study

Abstract: Introduction:The spectrum of multiple sclerosis (MS) among all its clinical types includes a vast number of alterations. Of these, respiratory impairment carries big implications since this is an important cause of mortality and morbidity. Methods: Here, we present an observational study of respiratory assessment through spirometry in individuals with MS. Subjects who underwent autologous hematopoietic stem cell transplant from an interventional study were considered to participate. Results: An abnormal patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This contribution found that 31% of patients recruited for HSCT, with no important comorbidities and factors related to pulmonary dysfunction had an abnormal spirogram, most frequently with a restrictive pattern. Of note, there was a significant association of predicted values of forced vital capacity and forced expiratory volume with EDSS and disease duration ( 18 ).…”
Section: Reports On Response and Clinical Evaluationmentioning
confidence: 99%
“…This contribution found that 31% of patients recruited for HSCT, with no important comorbidities and factors related to pulmonary dysfunction had an abnormal spirogram, most frequently with a restrictive pattern. Of note, there was a significant association of predicted values of forced vital capacity and forced expiratory volume with EDSS and disease duration ( 18 ).…”
Section: Reports On Response and Clinical Evaluationmentioning
confidence: 99%